Clinical outcomes of new toric trifocal diffractive intraocular lens in patients with cataract and stable keratoconus: Six months follow-up. Issue 12 (March 2017) - Farideh, Doroodgar; Azad, Sanginabadi; Feizollah, Niazi; Sana, Niazi; Cyrus, Alinia; Mohammad, Ghoreishi; Alireza, Baradaran-rafii
Abstract: Purpose: To evaluate the clinical results of toric trifocal diffractive intraocular lens in eyes with cataract and mild keratoconus. Methods: Five keratoconus patients (10 eyes) that had bilateral AT LISA 939 implantation were selected and had followed in 3-time horizons of 1, 3, and 6 months. Patients were 46 to 65 years old age, corneal astigmatism of (2.00 D at 6.75 D) and cataract that all of them needed cataract surgery. The distance, intermediate and near visual acuities, defocus curve, ocular aberrations, contrast sensitivity, were measured as effectiveness criteria. Results: Average of binocular uncorrected distance visual acuity (UDVA) improved from 0.72 log MAR ± 0.11 (SD) to 0.04 ± 0.04 ( P  < 0.05) log MAR, average of uncorrected binocular intermediate visual acuity (UIVA) (80 cm) improved from 0.52 ± 0.07 log MAR to 0.14 ± 0.04 ( P  < 0.05) log MAR, and average of binocular uncorrected near visual acuity (UNVA) improved from 0.48 ± 0.09 log MAR to 0.02 ± 0.07 ( P  < 0.05) log MAR at 6 months, respectively. Contrast sensitivity testing showed acceptable results, the binocular defocus curve corroborate were in appropriate good visual acuity even at the intermediate distances, by a gentle slope less than log MAR 0.2 at −1.5 D, with regard to the best distance visual acuity at the 0 D defocus. Conclusions: Trifocal AT LISA 939MP IOLs provided appropriate distances, near and intermediate of the visual results. Prediction of the refractive results and optical performances were good.